Familial Carney complex with embolic ischemic stroke: a case report and literature review - Luo, Tingting; Yin, Mengxing; Li, Lijin; Sun, Mengjiao; Li, Zhen; Li, Pengge; Liu, Mengmeng; Sun, Xinxin; Wu, Zhanyi; Liu, Yifan; Zhang, Lulu; Wang, Zhiyao; et al. (Frontiers in Oncology, 2025)
BackgroundCarney complex (CNC) is a rare autosomal dominant multiple neoplasia syndrome characterized by cutaneous and mucosal pigmented lesions, cardiac myxomas, and various endocrine and non-endocrine tumors.MethodsWe report a familial case of CNC presenting initially with embolic ischemic stroke. Comprehensive clinical evaluation, imaging studies, histopathological examination, and genetic analysis were performed on the proband and family members, with a literature review summarizing the clinical features of CNC.ResultsA pathogenic PRKAR1A mutation was identified in affected family members, who exhibited typical clinical features of CNC. The proband presented with stroke secondary to cardiac myxoma, highlighting the importance of early recognition in patients with multi-system manifestations.ConclusionsCNC should be suspected in young patients presenting with cardiac myxoma and stroke. Clinicians should maintain high vigilance for patients with multi-system symptoms and complex family histories. Comprehensive family history assessment and genetic testing facilitate early diagnosis of CNC.